2011
DOI: 10.3109/00207454.2010.526730
|View full text |Cite
|
Sign up to set email alerts
|

Pupil Light Reflex in Parkinson's Disease: Evaluation With Pupillometry

Abstract: We evaluated pupil light reflex (PLR) in patients with Parkinson's disease (PD) and normal controls by means of pupillometry and explored its possible relation to clinical characteristics in parkinsonian patients. PLR was evaluated using pupillometry in 66 patients with PD without clinical evidence of autonomic dysfunction and 44 healthy matched controls. PLR was elicited by single flash stimuli of 24.6 candelas/m(2) intensity and 20 ms duration, and six parameters were studied after full recording of pupil's … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
44
1
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 71 publications
(55 citation statements)
references
References 25 publications
1
44
1
1
Order By: Relevance
“…The significant decrease in these parameters indicates parasympathetic dysfunction in PD patients. These results are in agreement with our previous study in which we examined PLR in 66 PD patients [17]. In this study, discriminant analysis showed that ACmax was the most sensitive variable in order to discriminate PD patients and controls and the most suitable for the evaluation of parasympathetic function.…”
Section: Comparing Plr Parameters In Pd Patients and Controls We Fousupporting
confidence: 94%
See 1 more Smart Citation
“…The significant decrease in these parameters indicates parasympathetic dysfunction in PD patients. These results are in agreement with our previous study in which we examined PLR in 66 PD patients [17]. In this study, discriminant analysis showed that ACmax was the most sensitive variable in order to discriminate PD patients and controls and the most suitable for the evaluation of parasympathetic function.…”
Section: Comparing Plr Parameters In Pd Patients and Controls We Fousupporting
confidence: 94%
“…Stimulus duration was 20 ms and the luminance 24.6 candelas/m 2 . The SLE flash was placed in front of the eye at a distance of 30 cm [17].…”
Section: Pupillometry System and Experimental Conditionsmentioning
confidence: 99%
“…The previous studies explored that pupillary abnormalities may be occurred with diabetes, glaucoma, high myopia, demyelinating disease, autonomic neuropathy, Parkinson's disease, Alzheimer's disease, and so on [3][4][5][6][7][8][9]. The pupil reaction is affected by afferent and efferent function.…”
Section: Introductionmentioning
confidence: 99%
“…Currently smart phones are used to assess color vision, astigmatism, pupil size, macula integrity by the Amsler grid test, and fundus photography (Busis, 2010; Bastawrous, 2012; Bastawrous et al, 2012). Hence, an IR videography set-up coupled with a smart phone application seems an accessible approach in the assessment of the PLR in the clinical setting (Fotiou et al, 2000; Busis, 2010; Giza et al, 2011; Mohan et al, 2013). Such quantitative method is also more informative than the conventional technique using a pen torch, as the information could be used for future analysis and comparison.…”
Section: Introductionmentioning
confidence: 99%